2006
DOI: 10.1017/s003118200600151x
|View full text |Cite
|
Sign up to set email alerts
|

Host ecology and variation in helminth community structure in Mastomys rodents from Senegal

Abstract: We studied patterns of variation in parasite communities of 2 closely related species of Mastomys rodents. These 2 species live in sympatry in South-eastern Senegal, but differ drastically in their habitat choice. We asked (a) whether the host species have the same parasites; (b) whether there is any observable pattern relative to the host species/habitat type in the structure of parasite communities; (c) whether the variability in parasite community for each host species is related to habitat characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
5
45
2
Order By: Relevance
“…The species richness and prevalence of endoparasites observed in the current study was extremely low compared to that reported for other rodent hosts (Behnke et al, 1999;AbuMadi et al, 2000;Eira et al, 2006;Brouat et al, 2007;Froeschke et al, 2010). This may be linked to the aridity of the habitat that the study species exploits (annual mean: 400 mm) as it has been suggested that survival of free-living helminth stages is greatly reduced in such habitats due to desiccation (Eira et al, 2006;Froeschke et al, 2010).…”
contrasting
confidence: 84%
See 1 more Smart Citation
“…The species richness and prevalence of endoparasites observed in the current study was extremely low compared to that reported for other rodent hosts (Behnke et al, 1999;AbuMadi et al, 2000;Eira et al, 2006;Brouat et al, 2007;Froeschke et al, 2010). This may be linked to the aridity of the habitat that the study species exploits (annual mean: 400 mm) as it has been suggested that survival of free-living helminth stages is greatly reduced in such habitats due to desiccation (Eira et al, 2006;Froeschke et al, 2010).…”
contrasting
confidence: 84%
“…Alternatively, but not mutually exclusive, a greater proportion of juvenile individuals during the wet breeding season may explain the observed reduction of S. minuta burdens as a number of studies have reported an age-related accumulation of Syphacia sp. (Behnke et al, 1999;Eira et al, 2006;Brouat et al, 2007). Although we did not sample juveniles in our study, individuals of the youngest age class were almost exclusively observed during the wet season (Medger et al, 2010).…”
mentioning
confidence: 85%
“…At least one of these, the positive relationship between H. polygyrus and the species richness of other helminths in wood mice, has been demonstrated in three totally independent data-sets, two drawn from the UK and one from Portugal. The challenge now is to determine whether similar relationships exist for other heligmosomatids infecting other rodents in Europe where the helminth communities are generally depauperate and among host-parasite combinations in more distant parts of the world where helminth communities may be richer (Brouat et al 2007 but see also Behnke et al 2004). Nevertheless, whilst such relationships have already been shown to be repeatable, collectively they explain only a small percentage (usually less than 10 %) of the variance/deviance in abundance data.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Species such as M. natalensis are commensal and regularly invade human habitation whilst others are restricted to the grasslands, fields and the bush (Duplantier & Granjon, 1988;Brouat et al, 2007). Mastomys is one of the genera comprising the Praomys group of murine rodents, but their exact relationships to other genera natalensis (Smith, 1834), two species of Heligmonina have been described: H. chabaudi (Desset, 1964) and H. kotoensis Diouf et al, 2005, the latter being a coparasite with Neoheligmonella lamaensis Diouf et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst rodents of the genus Mastomys are known to carry a number of important bacterial and viral diseases that are transmissible to humans (Leirs, 1994), and some of their metazoan parasites have been reported (Ugbomoiko & Obiamiwe, 1991), including new species (Diouf et al, 1998(Diouf et al, , 2005, their helminth communities have only recently attracted attention (Brouat et al, 2007). Such studies are dependent on the accurate identification of the helminths infecting hosts, and in the case of Mastomys spp.…”
mentioning
confidence: 99%